Psychological and Behavioral Impact of Online Dating: A Literature Review - Nugroho, Umar Hamid; Islam, Azizah Fajar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Although the use of dating applications has increased rapidly, research examining their positive impacts remains limited compared to studies focusing on their negative consequences and psychological risks. The purpose of this study is to identify topics that have been previously explored and to determine research gaps within the topic of online dating. This study employed a literature review method. The researchers conducted several stages of literature search and selection focusing on empirical studies on online dating published within the last six years (2019–2025). The literature search was performed using the PubMed, Scopus, and Semantic Scholar databases. A total of 100 articles were identified in the initial search using the keyword “online dating” with the assistance of Publish or Perish software. After screening the titles and abstracts and conducting a more detailed review of the articles, the final results showed that only 11 articles met the criteria relevant to the research topic. The findings indicate that online dating is associated with various psychological risks, physical risks, coping strategies, positive outcomes, and its relationships with several behavioral and psychological problems. Future research is recommended to expand the scope of the literature and further explore the positive aspects of online dating to provide a more balanced and comprehensive understanding of this phenomenon.